Neuroblastic Tumors of the Adrenal Gland in Elderly Patients: A Case Report and Review of the Literature - Deslarzes, Philip; Djafarrian, Reza; Matter, Maurice; La Rosa, Stefano; Gengler, Carole; Beck-Popovic, Maja; Zingg, Tobias (Frontiers in Pediatrics, 2022)
Background Neuroblastic neoplasms (NN) include ganglioneuromas (GN), ganglioneuroblastomas (GNB), and neuroblastomas (NB). They generally arise in childhood from primitive sympathetic ganglion cells. Their incidence in adults, especially among elderly, is extremely low. Case Presentation This is the case of a 74-year-old woman with history of abdominal pain, weakness and night sweating since several months. Blood pressure was normal. CT-scan showed a 10 cm left adrenal mass, without other pathologic findings. An open left-sided adrenalectomy was performed. Recovery was uneventful with hospital length of stay of 8 days. Based on morphological, immunohistochemical, and molecular features the diagnosis was a nodular GNB. A positron emission tomography (PET) performed 6 weeks after the resection did not show any residual tumor or distant metastases. The patient was followed-up with annual clinical and radiological exams. Conclusion This case presentation, associated with a review of the literature, illustrates the importance to include NN in the preoperative differential diagnosis of adrenal tumors in adults and highlights the need for multidisciplinary patient work-up and management.